Answer: [tex]x^4-x^3-16x^2+16x[/tex]
Step-by-step explanation:
Factor theorem : If x=a is a zero of a polynomial p(x) then (x-a) is a factor of p(x).
Given: Zeroes of polynomial : -4,0, 1, and 4.
Then Factors = [tex](x-(-4)), (x-0), (x-1) and (x-4)[/tex] [By factor theorem ]
[tex]=(x+4), (x-0), (x-1) and (x-4)[/tex]
Multiplying these factors to get polynomial in standard form.
[tex](x+4)\times(x-0)\times(x-1)\times(x-4) \\\\= x(x+4)(x-4)(x-1)\\\\= x(x^2-4^2)(x-1)\\\\= x(x^2-16)(x-1)\\\\= x(x^2-16)(x-1)\\\\=x(x^2x+x^2\left(-1\right)+\left(-16\right)x+\left(-16\right)\left(-1\right))\\\\= x(x^3-x^2-16x+16)\\\\=x^4-x^3-16x^2+16x[/tex]
Hence, B is the correct option.